Исследование пространственного распределения 137Cs в почве в районе размещения Армянской АЭС - Р. М. Авакян; Г. Г. Арутюнян; В. А. Атоян; А. В. Овсепян; Э. В. Чубарян; К. И. Пюскюлян (ՀՀ ԳԱԱ հրատ.)
Исследовано содержание радиационно опасного радионуклида 137Cs в почве на территории радиусом 50 км, в том числе вблизи Армянской АЭС. Полученные данные хорошо согласуются с данными Научного Комитета по действию атомной радиации при ООН. The contents of radiation dangerous radionuclide 137Cs in soil on the territory with the radius of 50 km, including the area near the Armenian nuclear power plant, have been investigated. The obtained data, describing the net effect of the nuclear power plant on the population and environment, are in good agreement with data of the United Nations Scientific Committee of Radiation Action.
Keywords: Physics; Science; Nuclear Physics